Efektivitas Lama Perendaman Benih Menggunakan Cendawan Entomopatogen Terhadap Tanaman Secara Umum - Butar-Butar, Diva Slamat Christian; Vajri, Indri Yanil (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Entomopathogenic mushrooms (CEPs) double function as biocontrol agents against pests and as biostimulants that support plant growth through the production of hormones such as IAA and gibberelline. The application of CEP as a biostimulant can be done through seed treatment, with effectiveness greatly influenced by the type of mushroom and the duration of soaking. This study aims to evaluate the effect of the length of seed soaking in CEP suspension on germination, vigor index, and early plant growth. The three types of CEP used are Beauveria bassiana, Metarhizium anisopliae, and Trichoderma asperellum. Corn seeds are soaked in a conidia solution with a concentration of 1 × 10⁸ conidia/ml and sterile aqueducts for 3, 6, 12, and 24 hours. Observations were made on the percentage of sprouts (day 7), vigor index (day 12), and seedling growth (day 28). The results showed that soaking the seeds in CEP suspension was able to improve all growth parameters. Of the four durations tested, soaking for six hours gave the most optimal results in increasing germination, vigor, and early growth of corn plants.